2004
DOI: 10.2527/2004.82193x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, but not short-term, treatment with somatotropin during pregnancy in underfed pigs increases the body size of progeny at birth1

Abstract: Treatment of pigs with porcine ST (pST) in early to mid-pregnancy increases body weight and length of their fetuses by mid-pregnancy, but this increased weight may not persist to birth. We investigated the effects of short- (25 d) and long-term (75 d) treatment with pST, and interactions between long-term pST treatment and crude protein content of diet, in restricted-fed gilts. In both experiments, Large White x Landrace gilts were bred at first estrus to Large White x Duroc boars and allowed to farrow natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Increased fetal growth in pGH-treated dams in the present study is consistent with reports from previous studies of pGH in gilts, in which both placental and fetal growth increases have been reported at the end of treatment (Kelley et al 1995, Sterle et al 1995, Gatford et al 2000. Although litter average progeny birth weights or near term fetal weights are not increased when maternal pGH treatment stops around mid-pregnancy (Rehfeldt et al 1993, 2001b, Kelley et al 1995, Okere et al 1997, Gatford et al 2004, fetal and subsequent progeny development is altered and progeny from pGH-treated dams have larger muscles after weaning (Kelley et al 1995, Gatford et al 2003. In contrast with previous reports of greater progeny muscle development and placental length responses to pGH in small than in large littermates (Sterle et al 1995, Rehfeldt et al 2001a,b, Rehfeldt & Kuhn 2006, we found greater fetal growth responses to pGH in heavier littermates than in lighter littermates.…”
Section: Discussionsupporting
confidence: 91%
“…Increased fetal growth in pGH-treated dams in the present study is consistent with reports from previous studies of pGH in gilts, in which both placental and fetal growth increases have been reported at the end of treatment (Kelley et al 1995, Sterle et al 1995, Gatford et al 2000. Although litter average progeny birth weights or near term fetal weights are not increased when maternal pGH treatment stops around mid-pregnancy (Rehfeldt et al 1993, 2001b, Kelley et al 1995, Okere et al 1997, Gatford et al 2004, fetal and subsequent progeny development is altered and progeny from pGH-treated dams have larger muscles after weaning (Kelley et al 1995, Gatford et al 2003. In contrast with previous reports of greater progeny muscle development and placental length responses to pGH in small than in large littermates (Sterle et al 1995, Rehfeldt et al 2001a,b, Rehfeldt & Kuhn 2006, we found greater fetal growth responses to pGH in heavier littermates than in lighter littermates.…”
Section: Discussionsupporting
confidence: 91%
“…The increased neonatal size observed in the present study was consistent with that reported elsewhere in the literature (Rehfeldt et al 1993, Gatford et al 2004). This effect may have relevance to the prospect of using ST during pregnancy to treat intra-uterine growth retardation in humans, especially in the light of accumulating evidence of the adverse impact of low birth weight in adult life.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the placenta produces a variant of ST that progressively replaces pituitary ST in the maternal circulation from midgestation (Frankenne et al 1988), and has been correlated to birth weight in humans (Evain-Brion et al 1994, McIntyre et al 2000. In addition, fetal growth induced by maternal treatment with ST during early to mid-gestation may not necessarily be maintained to term (Gatford et al 2004), whereas treatment during the late or greater part of gestation has been related to increased piglet size at birth, as occurred in the present study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…So far efforts to manipulate maternal nutritional status centred on short periods before mating because a moderately high level of nutrition results in a maximized rate of ovulation. Since the 1970's it is also known that litter size and birth weight of pigs are relatively insusceptible to varied levels of maternal dietary protein intakes during gestation (Mahan and Mangan, 1975;Gatford et al, 2004) but it is uncertain whether gestational protein levels below or above sows' requirements have effects on performance traits later in life. In this context it is of interest that lower birth weight piglets (< 1.2 kg) from otherwise normal litters have later on lower daily gains, higher body fat contents, lower muscle mass and higher drip losses (Kuhn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%